Using Assistive Technology in Teaching Students with Disabilities - Salim Alhazmi, Huda (International Journal of Psychosocial Rehabilitation, 2024)
This paper was written to expose the meaning, benefits, and answer in what ways do laws, regulations, resources, district practices, and theoretical understandings of disability and special education influence accessibility and decision- making for students with disabilities in the area of assistive technology (AT)? The paper discussed promotes and detracts from understanding AT in schools and evidenced-based practices to implement AT. It pointed out the potential short term and long-term impact on learners with disabilities of utilizing concepts from WATI, Quality Indicators of AT, the assistive technology continuum (highlow tech), and the SETT Framework. It provided implications of influences (procedures, practices, resources, cost/funding, referral, professional development, attitudes/beliefs) on incorporating assistive technology in schools. It concluded that recommendations for how to address possible obstacles that may influence the implementation of AT in the IEP